Comparitive Benefits of Beekeeping Enterprise in Chitwan, Nepal - Pokhrel, Suroj (Journal of Agriculture and Environment, 2009)
Based on the survey cunducted in 2004, beekeepers in Chitwan had small and fragmented land holdings with lower rate of return from subsistence crop farming. They are keeping Apis mellifera L.in Langstroth hive in Terai and A. cerana Fab. in improved, traditional-log and wall hives in hills, for honey production purpose. The honey productivity in Terai was 3.54 folds higher (28.7 vs 8.1 kg/yr/hive) than in hills with highest average annual income in Bharatpur area followed by East and West Chitwan. Moreover, the income of the beekeepers in Chitwan from honey production was 3.62 folds higher than crop farming (NRs 83,996.88 vs NRs 23,214.22 /house hold/year). It clearly showed that beekeeping with A. mellifera in the Terai is potential enterprise for higher income compared to crop production. Key words: Annual income; Apiculture; Crop production; Honey productivity; Land holding The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 46-59